Millets as a Sustainable Solution for Nutritional Security: Study on Their Role in Food Systems and Human Health - Surendra Singh; Monu Sharma; Peeyush Raj Bangad (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This paper explores the use of millets in enhancing nutritional security and ensuring that people advance healthy lifestyles. As the world struggles with food insecurity challenges especially in the low and middle income countries, millets can play a wonderful role by providing a sensible sustainable food alternative to the popular staple food such as rice and wheat. The study was a pre and post intervention with a control group design to measure the health benefits of eating millet. The research was targeted to determine its effect on main health indicators related to blood glucose, cholesterol, body weight, and concentration of micronutrients. The samples were randomly selected and participants recruited were 150 in number; 75 in the experimental group (individuals that consume millet) and 75 in the control group (who do not consume millet). A group of the experiment took 50 grams of millet per day and received 3-6 months. The major results indicate that nutrient intake of millet resulted in markedly decreased blood glucose (-14.1 mg/dL), cholesterol (-15.3 mg/dL), and body weight (-3.7 kg) as compared to the control group. Also, the levels of micronutrients were effectively increased (iron, calcium, zinc). The belief in the health and sustainability advantages of millets was reported by the experimental group, which is consistent with their ability to address the issues of malnutrition and the necessity to have sustainable and climate-resilient agriculture. This paper highlights the promise of millets being a sustainable food that has the potential to meet the global nutrition challenge. It also reveals the need to have policy interventions and consumer education to introduce millets in mainstream diets and food systems towards sustainable nutritional security and health.
Keywords: Millets; Nutritional Security; Health Impact; Food Systems; Consumption Study; Pre/Post Intervention; Control Group